Immunological Study of Reconstructed Common Ancestral Sequence of Adenovirus Hexon Protein - Wang, Yingchen; Zhang, Zhe; Shang, Lei; Gao, Hong; Du, Xiqiao; Li, Falong; Gao, Ya; Qi, Guiyun; Guo, Weiyuan; Qu, Zhangyi; Dong, Tuo (Frontiers in Microbiology, 2021)
Aim: To reconstruct the ancestral sequence of human adenoviral hexon protein by combining sequence variations and structural information. And to provide an candidate hexon protein for developing new adenoviral vector capable of escaping the pre-existing immunity in healthy populations. Methods: The sequences of 74 adenovirus-type strains were used to predict the ancestral sequence of human adenovirus hexon protein using FastML and MEGA software. The three-dimensional structure model was built using homology modeling methods. The immunological features of ancestral loop 1 and loop 2 regions of sequences were tested using protein segments expressed in a prokaryotic expression system and polypeptides synthesized with human serum samples. Results: The tower region of the hexon protein had the highest sequence variability, while the neck and base regions remained constant among different types. The modern strains successfully predicted the common ancestral sequence of the human adenovirus hexon. The positive sera against neutralizing epitopes on the common ancestor of adenoviral hexon were relatively rare among healthy adults. Conclusion: The existing strains inferred the common ancestor of human adenoviruses, with epitopes never observed in the current human strains. The predicted common ancestor hexon is a good prospect in the improvement of adenovirus vectors.